IMPLEMENTATION OF NEW INTERNATIONAL STANDARDS FOR CERTIFICATION AND INSPECTION BODIES - Popović, Predrag; Popović, Dejana (Journal of Applied Engineering Science, 2014)
The paper provides a general review of accreditation as an effective and efficient means for provision of competence, impartiality, independence and integrity of conformity assessing organizations, which creates confidence of all interested parties into the results of testing, inspection and certification of products processes and services. Implementation of international standards, as the accreditation proceedings brought into accord, provides similar levels of competence of conformity assessing bodies in all states and obtaining comparable results, thus contributing, within different international and regional agreements, to the possibility of creating mutual recognition of conformity documents – i.e. reports and certificates. New requirements are presented brought about by the new standards of SRPS ISO/IEC 17065:2013 and SRPS ISO/IEC 17020:2012, as well as their application in the certification and inspection body Vinca Institute.